ANALISIS QUALITY PRINCIPLE TERHADAP KINERJA TOTAL QUALITY MANAGEMENT PADA PT. IVO MAS TUNGGAL DUMAI - Reinaldo, Rio; Marpaung, Rio J.M.; Paramitha, Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of Countinious Improvement, Just In Time System and Benchmarking on organizational performance at PT. Ivo Mas Tunggal Dumai Bulking Dumai City. The data was collected by distributing questionnaires to 74 respondents. Analytical technique using multiple linier regression analysis method. The results showed that the Countinious Improvement variable significantly influenced Performance. Further research results show that the variable Just In Time System has a significant effect on Performance. Further research results indicate that Benchmarking has a significant effect on Performance. Countinious Improvement variables, Just In Time System and Benchmarking affect the change in performance value by 82%. While the remaining 18% is influenced by other variables that are not included in this regression model. Keywords : Countinious Improvement, Just In Time System, performance